Juridical Analysis Of The Authority Of Quarantine Officers In Handling Illegal Importation Of Caws On Batam Island - Erniyanti Erniyanti; Yulia Hardhiyanti Putri (FKIP, Universitas Palangka Raya, 2023)
Quarantine is a system of preventing the entry, exit, and spread of quarantined animal pests and diseases, as well as supervision and control of food safety and food quality, feed safety and feed quality, Genetic Engineering products, Genetic Resources, Biological Agents, Invasive Foreign Species, Wild Plants and Animals, and Rare Animals that are introduced into, spread from one area to another area, and removed from the territory of the Unitary State of the Republic of Indonesia. To maintain, protect, and improve the quality of animal/livestock resources, animal/livestock health, animal welfare, and the provision of safe, healthy, whole, and halal (ASUH) food of animal origin, as well as maintaining peace or eliminating/preventing public unrest, it is necessary to provide guidance, regulation, control, and supervision of livestock businesses and animal health services. To create a conducive business climate and legal certainty in animal husbandry and animal health, it is necessary to regulate the mechanisms and procedures for licensing livestock and animal health businesses in the regions. The problem faced by the Batam Class I Agricultural Quarantine Center is caused by cows entering Batam Island that do not have an entry permit and are not by Law Number 21 of 2019, which states that every entry or release must be carried out through a designated Place of Entry and Place of Expenditure.